Evolutionary computation, machine learning and data mining in bioinformatics 9th European conference, EvoBIO 2011, Torino, Italy, April 27-29, 2011. proceedings - Pizzuti, Clara; Ritchie, Marylyn D.; Giacobini, Mario (Lecture notes in computer science, 2011)
This book constitutes the refereed proceedings of the 9th European Conference on Evolutionary Computation, Machine Learning and Data Mining in Bioinformatics, EvoBIO 2011, held in Torino, Italy, in April 2011 co-located with the Evo 2011 events. The 12 revised full papers presented together with 7 poster papers were carefully reviewed and selected from numerous submissions. All papers included topics of interest such as biomarker discovery, cell simulation and modeling, ecological modeling, fluxomics, gene networks, biotechnology, metabolomics, microarray analysis, phylogenetics, protein interactions, proteomics, sequence analysis and alignment, and systems biology.